C2028T polymorphism in exon 12 and dinucleotide repeat polymorphism in intron 13 of the HIF-1alpha gene define HIF-1alpha protein expression in non-small cell lung cancer. - Koukourakis, M; Papazoglou, D; Giatromanolaki, A; Panagopoulos, I; Maltezos, E; Harris, A; Gatter, K; Sivridis, E (2006)
OBJECTIVES: In this study, we investigated whether polymorphisms of the HIF-1alpha gene may account for the patterns of HIF-1alpha protein expression in non-small cell lung carcinomas (NSCLC) and the expression of HIF-1alpha down-stream proteins. METHODS: Specific HIF-1alpha polymorphisms were assessed in a series of patients with NSCLC: (a) the C to T transition at nucleotide 1744 (position 2028 according to sequence with accession number , which gives rise to Pro/Ser variation at codon 582), (b) the G to A nucleotide substitution at point 1790 (position 2046 according to sequence with accession number , which gives rise to Ala/Thr variation at codon 588), and (c) the dinucleotide GT repeat polymorphism in intron 13. Immunohistochemistry for HIF-1alpha and down-stream proteins (VEGF, LDH-5, GLUT-1) was also performed in tumor material. RESULTS: A strong association of the P582S polymorphism and of GT repeat polymorphism higher than 14/14 with increased HIF-1alpha expression was noted. HIF-1alpha polymorphism did not relate to the expression of the HIF-1alpha downstream proteins analysed, but significant association of HIF-1alpha expression with LDH-5 was confirmed (p=0.008). CONCLUSIONS: HIF-1alpha polymorphisms may have an important impact on HIF-protein stability and, eventually, function.